2016
DOI: 10.1007/s00408-016-9949-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Forced Oscillation Technique for Evaluation of Small Airway Disease in Interstitial Lung Diseases

Abstract: UMIN 000020733.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…58,59 In a study by Mori et al, 60 decreased X values (especially X5) were found in patients with ILD, mostly in inspiration, which has more negativity than in expiration, in contrast to patients with COPD, which had decreased values in expiration that is more negative than in inspiration. A Japanese study conducted by Mikamo et al 61 showed that oscillometry may be a useful tool in assessment of small airways disease in interstitial lung disease. A very recent study, conducted by Reham et al, 62 studied correlations between oscillometry and spirometry on patients diagnosed with rheumathoid arthritis accociating ILD, and concluded that IOS can be used as an early screening technique to identify proximal and distal pulmonary tissue affection even before spirometry changes appear.…”
Section: Interstitial Lung Disease (Ild)mentioning
confidence: 99%
“…58,59 In a study by Mori et al, 60 decreased X values (especially X5) were found in patients with ILD, mostly in inspiration, which has more negativity than in expiration, in contrast to patients with COPD, which had decreased values in expiration that is more negative than in inspiration. A Japanese study conducted by Mikamo et al 61 showed that oscillometry may be a useful tool in assessment of small airways disease in interstitial lung disease. A very recent study, conducted by Reham et al, 62 studied correlations between oscillometry and spirometry on patients diagnosed with rheumathoid arthritis accociating ILD, and concluded that IOS can be used as an early screening technique to identify proximal and distal pulmonary tissue affection even before spirometry changes appear.…”
Section: Interstitial Lung Disease (Ild)mentioning
confidence: 99%
“…If the small airway lesion is present, the resistance is increased and more negative shift of reactance at low frequency, and the interstitial changes cannot be reflected. Mikamo et al28 reported that the 90 patients with ILD were divided into the two groups according to the presence or absence of small airway disease findings detected by HRCT, and the impedance parameters were compared. The absolute values of R5–R20, X5, and ƒres were elevated in ILD patients with small airway disease compared to those without small airway disease.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic pulmonary fibrosis (IPF) is a specific form of chronic, progressive, fibrosing interstitial pneumonia of unknown cause with a poor prognosis [1][2][3]. Since the clinical course of individual patients with IPF varies [4], many studies have been reported regarding developing clinical, physiological, and radiological markers to evaluate the clinical conditions and prognosis of patients with IPF [5][6][7][8][9][10][11][12][13][14][15][16][17]. As radiological and physiological markers, fibrosis-related high-resolution computed tomography (HRCT) findings and pulmonary function tests are used for predicting the prognosis of patients with IPF [10,11,13,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these markers, studies for evaluating patients with IPF using oscillometry, also called the forced oscillation technique, have been reported [14,15].…”
Section: Introductionmentioning
confidence: 99%